(untitled) (Economics and region, 2022)
This article examines the essence of the concept of " гesiliency", the main points of view of scientists regarding the solution of economic problems of the гesiliency of enterprises, considers various methodological approaches to the study of the level of viability of a seaport: based on the concept of the viability of socio-economic systems, which is a function of assessments of its stability, reliability, vitality and motivation. On the basis of this approach, a study of the viability of the state enterprise "Commercial Sea Port "Chornomorsk" was conducted, it can be said that in general the port has a low level of viability. The second approach is based on the study of the strategic sustainability of the seaport, that is, the calculation and analysis of the level of sustainability of the enterprise as a whole, as well as all the subsystems of the port’s activity. For this approach, the author proposed a system of indicators for assessing the sustainability of the main types of activities of the sea port, compiled taking into account the specifics of the activities of maritime transport enterprises. The third approach is based on assessment of factors affecting the profitability of the port using economic and statistical modeling. Each of these methods is scientifically based and provides an opportunity to assess the degree of influence of industrial and economic activity on the level of гesiliency of the seaport. this methodical approach allows you to assess the impact of the listed factors on the formation of the effective indicator of the seaport’s income and to analyze the state of the economic, production and personnel components of its viability. Using this methodology and having statistical information from financial and economic reports [10], for example, let’s build a multifactor model for the state enterprise "Commercial Sea Port «Yuzhniy»”. It was found that the volume of loading and unloading works has the greatest quantitative influence on the formation of income, and the costs have an inversely proportional effect on the amount of income of the sea port, which is confirmed in practice.